Role of Uptake Transporters OAT4, OATP2A1, and OATP1A2 in Human Placental Bio-disposition of Pravastatin - Fokina, Valentina M.; Patrikeeva, Svetlana; Wang, Xiao ming; Noguchi, Saki; Tomi, Masatoshi; König, Jörg; Ahmed, Mahmoud S.; Nanovskaya, Tatiana (Journal of Pharmaceutical Sciences, 2021)
Pravastatin is currently under evaluation for prevention of preeclampsia. Factors contributing to placental disposition of pravastatin are important in assessment of potential undesirable fetal effects. The purpose of this study was to identify the uptake transporters that contribute to the placental disposition of pravastatin. Our data revealed the expression of organic anion transporting polypeptide 1A2 (OATP1A2) and OATP2A1 in the apical, and OATP2B1 and OATP5A1 in the basolateral membranes of the placenta, while organic anion transporter 4 (OAT4) exhibited higher expression in basolateral membrane but was detected in both membranes. Preloading placental membrane vesicles with glutarate increased the uptake of pravastatin suggesting involvement of glutarate-dependent transporters such as OAT4. In the HEK293 cells overexpressing individual uptake transporters, OATP2A1, OATP1A2 and OAT4 were determined to accept pravastatin as a substrate at physiological pH, while the uptake of pravastatin by OATP2B1 (known to interact with pravastatin at acidic pH) and OATP5A1 was not detected at pH 7.4. These findings led us to propose that OATP1A2 and OATP2A1 are responsible for the placental uptake of pravastatin from the maternal circulation, while OAT4 mediates the passage of the drug across placental basolateral membrane in the fetal-to-maternal direction.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Drug transport; In vitro model; Kinetics; Membrane transport; Membrane transporters; Organic anion transporter(s); Organic anion transporting polypeptide(s); Placenta; Pregnancy; Transporter(s)